Laboratory Tests of the Area of Head Joints and Bed Joints Increase the Diagonal Shear Stress of Brick Walls - Marwahyudi, Marwahyudi; Rifai, Muhammad Dian; Ahwan, Ahwan (ASTONJADRO, 2024)
The strength of a brick wall is influenced by the failure of the mortar bond and the resistance of the bad joint and head joint when carrying the force. The wider the head joint and bad joint areas result in a wider bonded area which increases the diagonal shear strength of the wall. Residential walls that have increased ability to withstand diagonal shear forces will be more stable when subjected to earthquake lateral forces. This research formulates that the wider the connecting area of the body and head joint, the higher the diagonal shear strength. The test was carried out by making a square test object measuring 60 x 60 cm. then pressure is applied in the diagonal direction. At the time of setting up the test object is done carefully and thoroughly. The test object is positioned perpendicular to the diagonal direction. The test object is placed absolutely perpendicular and is given a load until it is completely damaged. Loading method by providing a force that increases regularly until the structure experiences a complete failure. The bonded area in each brick shape is measured and compared with the results of the diagonal shear strength. This value is analyzed to obtain the effect on the diagonal shear strength. The percentage effect of each brick shape is compared and the results are analyzed. The results of the analysis are to obtain justification whether the area of the bad joint and head joint affects the diagonal shear strength. The novelty of this research is to obtain several brick designs that increase the strength of the diagonal shear stress. Tests show that the greater the area of the head joint, the greater the value of the diagonal shear stress.